O'Leary Series: Microsoft Office Word 2003 Brie - J. OLeay Timothy (MC Graw Hill, 2003)
The goal of the O’Leary Series is to give students a basic understanding of computing concepts and to build the skills necessary to ensure that information technology is an advantage in whatever career they choose in life. The O’Leary Microsoft Office 2003 texts are crafted to be the true step-by-step way for students to develop Microsoft Office application skills. The text design emphasizes step-by-step instructions with full screen captures that illustrate the results of each step performed. Each Tutorial (chapter) combines conceptual coverage with detailed software-specific instructions. A running case that is featured in each tutorial highlights the real-world applications of each software program and leads students step-by-step from problem to solution.